Effect of wind speed on evaporation rate in air conditioner based desalination units - Ibnu Sulistiono; Dan Mugisidi; Nurkholid; Oktarina Heriyani (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
Due to environmental changes, ensuring access to clean water is challenging for many regions. This study examines how wind speed influences seawater evaporation rates in a desalination system. Conducted indoors, the research varied wind speeds (0.6 m/s, 0.7 m/s, and 0.8 m/s) while maintaining a consistent temperature. A modified window Air Conditioner (AC) served as the evaporation unit, with its condenser immersed in water to utilize released heat, and its evaporator used as a condenser. Water temperature was maintained at 60-70°C. Results demonstrated a significant increase in evaporation rates with higher wind speeds. The strong correlation between experimental and theoretical results underscores wind speed as a critical factor in enhancing freshwater production efficiency from seawater. These insights inform the design of more effective desalination systems, offering potential solutions to water scarcity challenges in vulnerable regions